Influence of local and landscape characteristics on the distribution and diversity of fish assemblages of streams in the Ivinhema River basin, Upper Paraná River - Lemke,Ana Paula (2013)
OBJECTIVES: Among the most relevant issues in community ecology is the influence of different ways of addressing the pattern of diversity and distribution of species, and based on this, the present study sought to evaluate the influence of landscape and local characteristics on the richness and composition of fish assemblages in the Ivinhema River basin. METHOD: In the present study, we used data of distribution of fish species in 25 stretches of streams of the Ivinhema River basin, Upper Paraná River, aiming to know the role of local characteristics and land use on fish assemblages. RESULTS: We identified 113 fish species, and those sampled in a greater number of sites were: Astyanax altiparanae and Serrapinnus notomelas. The richness varied between 4 and 65 species. The regression tree allowed explaining 89.3% of richness variation, and permitted to identify that altitude is the main predictor of richness. According to the canonical correspondence analysis, variables that most influenced the species distribution were: altitude, depth, width, velocity, conductivity and percentage of built-up areas. CONCLUSIONS: Our results suggested that factors that most influenced fish assemblages in the Ivinhema River basin were physiographic and limnological characteristics, followed by land use.